국내외 사전의 인용례 현황 검토 - 김지혜(Kim, Jihye); 박도리(Bak, Do Rhee); 윤지솔(Yun, Jisol) (한국사전학, 2024)
이 연구는 국내외 주요 사전의 인용례 기술 현황을 조사하여 비교·검토하고, 이를 바탕으로 국어사전의 인용례가 지니는 현실성·동시대성·균형성 결여의 문제를 개선할 수 있는 방향을 제안하는 것을 목적으로 하였다. 국어사전 3종과 영어, 일본어, 프랑스어, 독일어 각 1종씩 4개 언어의 사전을 검토한 결과, 국내외 주요 사전의 인용례 출처는 주로 문학 작품이지만, 국외 사전에서는 신문 기사, 서간, 전문 서적 등으로 출처를 확대해 가고 있는 경향이 확인되었다. 한편 국어사전 인용례를 개선하기 위해서는 인용 출전의 목록을 최신화하고 인용 출처를 확대할 필요가 있음을 제안하였다. 이 연구는 국외 주요 사전들의 가장 최신 버전의 인용례 현황을 밝힌 점과, 국어사전 인용례의 현황을 구체적으로 통계화한 점, 개선이 필요한 문제점을 객관적으로 밝혀낸 점에서 의의를 지닌다. 이에 향후 국어사전 용례 연구에서 의미 있는 기초 연구가 될 것으로 기대된다. This study compares the examples and quotations in major domestic and foreign dictionaries. Based on the findings, we aim to propose what can be improved about quotations in Korean dictionaries to reflect the linguistic reality, contemporaneity, and balance. Upon reviewing three Korean dictionaries and one dictionary each for English, Japanese, French, and German, it was confirmed that foreign dictionaries tend to expand their sources to include not only literary works but also newspaper articles, letters, and professional publications. We suggest that the list of citation sources in Korean dictionaries be updated and the range of source genres expanded. We believe this study holds significance in that it provides a detailed statistical overview of quotations in Korean dictionaries and identifies the areas to be improved. In addition, by reviewing recent quotations of major web-based dictionaries, we expect this study to serve as a meaningful foundation for future research. KCI Citation Count: 0